Modelling domestic water demand: An agent based approach. (May 2016) - Koutiva, Ifigeneia; Makropoulos, Christos
Abstract: The urban water system is a complex adaptive system consisting of technical, environmental and social components which interact with each other through time. As such, its investigation requires tools able to model the complete socio-technical system, complementing "infrastructure-centred" approaches. This paper presents a methodology for integrating two modelling tools, a social simulation model and an urban water management tool. An agent based model, the Urban Water Agents' Behaviour, is developed to simulate the domestic water users' behaviour in response to water demand management measures and is then coupled to the Urban Water Optioneering Tool to calculate the evolution of domestic water demand by simulating the use of water appliances. The proposed methodology is tested using, as a case study, a major period of drought in Athens, Greece. Results suggest that the coupling of the two models provides new functionality for water demand management scenarios assessment by water regulators and companies. Highlights: A methodology exploring the evolution of domestic water demand behaviour and its interactions with the urban water system. A new model, the Urban Water Agents' Behaviour model, is developed to simulate the domestic water users' behaviour. The Urban Water Optioneering Tool is used to calculate the evolution of domestic water demand. The coupling of the two models is applied in the city of Athens, Greece. Results show potential in supporting water regulators and companies to design effective water demand management campaigns.